Overview of Risk Factors Uterine Prolapse: A Literature Review - Nisrina Salimah Putri; Eighty Mardiyan Kurniawati; Budi Utomo; Gatut Hardianto (Journal of Community Medicine and Public Health Research, 2026)
Uterine prolapse, a subtype of pelvic organ prolapse (POP), is characterized by the descent of the uterus into the vaginal canal due to weakening of pelvic floor support and connective tissues. Globally, POP affects approximately 2–20% of women, with higher prevalence reported in low- and middle-income countries, and uterine prolapse remains a significant contributor to morbidity among multiparous and postmenopausal women. Although not life-threatening, this condition substantially impairs quality of life through sexual dysfunction, urinary and bowel symptoms, and significant psychological distress. The purpose of this literature review is to summarize and analyze risk factors for uterine prolapse, with an emphasis on obstetric, biological, sociodemographic, and lifestyle factors consistently reported in recent research. A literature search was conducted using Google Scholar, PubMed, and ScienceDirect, and relevant articles published between 2018 and 2024 were identified, using keywords such as "pelvic organ prolapse," "uterine prolapse," and "risk factor." The findings indicate that multiparity, vaginal delivery, advancing age, menopause, obesity, and heavy physical workload are the most reported risk factors. Furthermore, chronic increases in intra-abdominal pressure and genetic predisposition have also been identified as contributing factors in several studies. Understanding these multifactorial determinants is essential for healthcare providers to implement early prevention measures, provide better patient education, and improve the overall management of uterine prolapse, thereby enhancing the wellbeing of affected women across various clinical settings.